Strength Abilities and Serve Reception Efficiency of Youth Female Volleyball Players - Damian Pawlik; Wioletta Dziubek; Łukasz Rogowski; Artur Struzik; Andrzej Rokita (Applied Bionics and Biomechanics)
Success in volleyball largely depends on motor abilities, particularly on maximum strength, power, jumping, and speed performance. However, a small number of studies assess the relationship between motor abilities and the effectiveness of volleyball technical skills. Therefore, the aim of the study was to assess the impact of the strength of the upper and lower limbs on the efficiency of serve reception during a 2 vs. 2 game, as well as to evaluate the results of motor measurements in the context of determining the usefulness of current testing procedures. The study involved a carefully chosen group of 12 girls aged 12–13 years (body height: 176.5±4.2 cm, body mass: 58.6±5.1 kg, and training experience: 43±15 months) selected for the Lower Silesian Regional Volleyball Team. The following tests were conducted: handgrip strength with a hand dynamometer, bent-arm hang, 2 kg medicine ball throw, shoulder joint internal rotators (IR) peak torque, standing long jump, spike jump, and countermovement jump. The measurements of the shoulder joint IR peak torque were performed under isometric (at 10°, 35°, and 65° rotation angles) and isokinetic (at 60°/s, 180°/s, and 300°/s) conditions. The efficiency of serve reception was evaluated during a 2 vs. 2 games by using Data Volley statistical software. The strongest positive relationships were observed between the serve reception efficiency and the peak torque and power of the shoulder joint IR, the medicine ball throw distance, and handgrip strength. Jumping variables showed no associations with efficient of serve reception. Consequently, we suggest adding protocols to volleyball training that include strength exercises aimed at developing the IR muscle group. The isokinetic upper limb test should be introduced as a valid tool in selection process. Coaches who do not have access to modern research equipment should use the medicine ball throw test to evaluate strength abilities as an alternative assessment of the serve reception efficiency.